Positronium impact excitation of hydrogen molecule to B-1 Sigma(+)(u) and b(3)Sigma(+)(u) states - Biswas, P. K.; Adhikari, S. K. (Iop Publishing Ltd, 1998)
Calculation for the electronic excitation of the ground state of H-2 to B (1) Sigma(u)(+) and b(3) Sigma(u)(+) states by positronium- (Ps) atom impact has been carried out using the first Born approximation considering discrete Ps excitations up to n = 6 and Ps ionization in the final state. To include the effect of electron exchange, we propose an alternative approximation scheme in the light of the Rudge approach, which takes into account the composite nature of the Ps-atom projectile.